EMT-driven plasticity prospectively increases cell–cell variability to promote therapeutic adaptation in breast cancer - Lauriane Muller; Frédérique Fauvet; Christelle Chassot; Francesca Angileri; Angèle Coutant; Cyril Dégletagne; Laurie Tonon; Pierre Saintigny; Alain Puisieux; Anne-Pierre Morel; Maria Ouzounova; Pierre Martinez (Cancer Cell International)
Abstract Cellular plasticity enables cancer cells to adapt non-genetically, thereby preventing therapeutic success. The epithelial-mesenchymal transition (EMT) is a type of plasticity linked to resistance and metastasis. However, its exact impact on population diversity and its dynamics under chemotherapy is unknown. We used single-cell transcriptomics to investigate phenotypic diversity dynamics upon treatment in two in vitro models of triple negative breast cancer (TNBC), where EMT-driven plasticity is either induced or spontaneously occurring. We report that EMT-driven plasticity confers higher phenotypic cell–cell variability (p < 0.001) while enriching for stem-like cells. Genetic and phenotypic cell–cell variability were not consistently correlated. High-plasticity populations displayed more pre-adapted cells before treatment (p = 0.03). In a population displaying spontaneous EMT and phenotypic variation, pre-adapted cells were a rare minority of high-scoring outliers whose expression patterns correlated with survival in TNBC patients subjected to chemotherapy (p = 0.03). Higher plasticity was not associated with a partial EMT status. Our results provide novel insights on how EMT-driven plasticity promotes a prospective diversification process increasing population phenotypic diversity, which can yield rare pre-adapted states before treatment. This highlights the need to tackle phenotypic diversity prior to treatment in high-plasticity tumours.